Analysis and Implementation of Backup Line Network Using Branch Office VPN and Speedy Internet Broadband - Kotim Subandi; Adriana Sari Aryani (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2018)
The purpose of this research is to build computer network infrastructure that connects between head office and branch office (Site), so that all network connection performance can be upgraded to help and support the company's business objectives. In order for these needs can be met well and can overcome the problems of technology failure when communication and information exchange is underway, the technology will be used is a connection that can always be online with the aim that quality in service approaching 100% (service excellent). Network Infrastructure to be implemented is to use two lines of connection, the first is to use Telkom Metro Ethernet, and the second connection Branch Office VPN by using internet line broadband speedy from Telkom, if one of the connection down then the other connection as a backup, and if both connections are in stable and good condition, it can be ascertained both connections can serve conveying data simultaneously. Which is used to set the two connections in the topology holder built head office with Head Office(Site)is Cisco Router